2011
DOI: 10.1111/j.1398-9995.2011.02670.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary brain tumours and specific serum immunoglobulin E: a case–control study nested in the European Prospective Investigation into Cancer and Nutrition cohort

Abstract: The results, based on serum samples prospectively collected in a cohort study, provide some support for the hypothesis that individuals with allergic sensitization are at reduced risk of glioma and confirm results from previous case-control studies. DOI: https://doi.org/10.1111/j. 1398-9995.2011.02670.x Posted at the Zurich Open Repository and Archive, University of Zurich ZORA URL: https://doi.org/10.5167/uzh-54311 Originally published at: Schlehofer, B; Siegmund, B; Linseisen, J; Schüz, J; Rohrmann, S; Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 35 publications
3
69
1
Order By: Relevance
“…A series of cohort studies have also suggested that hay fever/allergic rhinitis may be protective against glioma, although results from these studies did not reach statistical significance (likely due to small numbers of cases) (3). Additionally, a case-control study nested in the European Prospective Investigation into Cancer and Nutrition Cohort (EPIC) found an OR of 0.73 for having specific IgE against the eight most common respiratory allergens (using pre-diagnostic specimens), though this finding was not statistically significant (95% CI: 0.51–1.06) (15). Similarly, Wiemels et al reported an odds ratio of 0.73 (95% CI: 0.56–0.96) associated with a positive history of at least one self-reported respiratory allergy (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of cohort studies have also suggested that hay fever/allergic rhinitis may be protective against glioma, although results from these studies did not reach statistical significance (likely due to small numbers of cases) (3). Additionally, a case-control study nested in the European Prospective Investigation into Cancer and Nutrition Cohort (EPIC) found an OR of 0.73 for having specific IgE against the eight most common respiratory allergens (using pre-diagnostic specimens), though this finding was not statistically significant (95% CI: 0.51–1.06) (15). Similarly, Wiemels et al reported an odds ratio of 0.73 (95% CI: 0.56–0.96) associated with a positive history of at least one self-reported respiratory allergy (20).…”
Section: Discussionmentioning
confidence: 99%
“…These associations have been examined using single- [i.e., (11)], multi-site [i.e., (1214)], and nested case-control studies [i.e., (15, 16)], prospective cohort studies [i.e., (3)], and meta-analyses [i.e., (1, 2, 7)]. Additionally, the observed inverse association between allergies and glioma has remained consistent across studies with different exposure assessment strategies, such as self-reported allergy status (3), self-reported physician-diagnosed allergies (12, 13, 1719), number of allergy types (12, 17), and allergy-related biomarkers, such as Immunoglobulin E [overall (4, 11, 16, 20), pre-diagnostic (16, 21), and/or allergen-specific (11, 15, 16)], soluble CD23 levels (22), and polymorphisms in allergy-related genes (2326). As the literature approaches a consensus on the relationship between allergies and glioma risk, our large consortium, the Glioma International Case-Control Study (GICC), provides an unprecedented opportunity to not only confirm the previously reported associations between atopy and glioma in the largest available study population, but also to hone in on the specific role of respiratory allergies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies the levels of IgE, an objective assessment tool for allergic conditions, correlated with the risk for glioma. The risk increased inversely with the levels of IgE (100,(103)(104)(105). It seems that function of immune cells is altered in patients with GBM, in the sense that instead of preventing tumor appearance, immunity mechanisms support it (106).…”
Section: Allergies Atopic Conditions Infections Other Disease Medmentioning
confidence: 93%
“…Recent studies have consistently indicated an inverse association between self-reported allergies or atopic disease and glioma risk [3][4][5][6]. Moreover, evidence has also suggested that elevated immunoglobulin E (IgE) levels are associated with lower glioma risk [7,8]. Given the consistent epidemiological data supporting the relationship between allergy and glioma, it has been hypothesized that inflammation-related cytokines, which are critical for allergy and IgE production, and their single nucleotide polymorphisms (SNPs) may alter the risk of glioma by affecting the body's immune status.…”
Section: Introductionmentioning
confidence: 99%